Pesticide Exposure and Oxidative Stress Biomarkers Among West Java Applicators - Jen Fuk Liem; Susanty Dewi Winata; Johannes Hudyono; Gestinfiani Phang; Chelsea Jeconia Yuti Tanggo (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
Pesticide exposure may induce oxidative stress, which subsequently contributes to the onset of chronic diseases. This study aimed to evaluate the association between pesticide exposure intensity and oxidative stress among pesticide applicators using urinary malondialdehyde (MDA) and 8-hydroxy-2′-deoxyguanosine (8-OHdG) as biomarkers. A total of 74 vegetable farmers who had actively applied pesticides for at least one year were included in this cross-sectional study. The cumulative exposure level (CEL) of pesticides was estimated using a validated quantitative method. Urinary MDA and 8-OHdG were analyzed at an accredited testing laboratory. The Mann-Whitney U test was used to assess differences in MDA and 8-OHdG levels in the study population by individual and occupational characteristics. The mean age was 51.2 years (SD 11.3). Pesticide applicators were exposed to multiple pesticide classes, and the use of complete PPE was low. Higher cumulative pesticide exposure (CEL) was associated with increased oxidative stress, reflected by elevated urinary MDA and 8-OHdG, with different biomarkers capturing distinct exposure dimensions. This finding shows the need for comprehensive preventive strategies that focus on reducing exposure intensity through safer work practices, complemented by the appropriate use of personal protective equipment and ongoing education.